HYGINIE, SANITATION AND NUTRITION OF SNACKS IN THE CANTEEN - Rahayu, Tutiek; Fauzan, Aji Nur Nur; Pertiwi, Kartika Ratna (Universitas Negeri Yogyakarta, 2023)
The purpose of this study was to determine the sanitation hygiene of the school canteen, the contribution of wet snack food to meeting the daily nutritional needs of students and to find out whether there were differences in sanitation and nutritional hygiene between wet snacks sold in the school canteen between Adiwiyata school canteens and non-Adiwiyata schools. This type of research is a descriptive observational research. The sample in this study is packaged and unpackaged snacks which are often sold in the school canteen. The variables in the study were the condition of the snacks in SD Adiwiyata and SD non-Adiwiyata in Bantul Regency. The standard instrument from the Indonesian Ministry of Health regarding hygiene, sanitation and nutritional content of food uses a computer application